2004
DOI: 10.1021/la036274s
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Deposition and Surface Characterization of Oligoglyme, Dioxane, and Crown Ether Nonfouling Films

Abstract: Plasma-deposited PEG-like films are emerging as promising materials for preventing protein and bacterial attachment to surfaces. To date, there has not been a detailed surface analysis to examine the chemistry and molecular structure of these films as a function of both precursor size and structure. In this paper, we describe radio-frequency plasma deposition of a series of short-chain oligoglymes, dioxane, and crown ethers onto glass cover slips to create poly(ethylene glycol)-like coatings. The resultant fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
113
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(142 citation statements)
references
References 41 publications
23
113
2
1
Order By: Relevance
“…This phenomenon has been previously shown by Johnston, et al, [39] where they successfully correlated protein resistance with ether carbon content.…”
Section: Discussionsupporting
confidence: 78%
“…This phenomenon has been previously shown by Johnston, et al, [39] where they successfully correlated protein resistance with ether carbon content.…”
Section: Discussionsupporting
confidence: 78%
“…The low protein adsorption in this study compared with those reported in the current study could be attributed to a higher C-O component (84%), lower protein concentrations and differences in plasma-processing parameters such as the pulsed plasma conditions and the use of a tetraglyme monomer [30]. Previous studies have shown that tri-and tetraglyme plasma polymer films are extremely effective in reducing surface protein adsorption [15,20]. , for which the oxygen content is higher (33% O, 67% C).…”
Section: Characterization Of the Films Using Atomic Force Microscopycontrasting
confidence: 56%
“…It appears that, with regards to the di(ethylene glycol) dimethyl ether plasma polymer films, surface tension effects are not a significant discriminating factor in their relative water solvation and protein-fouling characteristics, as has been previously reported [15,31]. In a study on plasma polymer films deposited from ethylene glycolcontaining monomers, Johnston et al [15] have shown that molecular surface structure primarily affects the ability of PEG-like plasma polymer films to resist protein adsorption. Little correlation was observed between the contact angles measured and protein adsorption, suggesting that surface tension and interfacial tension effects are not the primary factors that influence protein adsorption and water solvation in these types of plasma polymer thin films.…”
Section: % Compositionmentioning
confidence: 83%
“…The biocompatibility of the micontainers can be further enhanced by precisely controlling the materials used, surface chemistry and shape. One such approach would be to coat the entire self-assembled 3D microcontainer with a layer of an inert metal (by electrodeposition), oxide (by chemical vapour deposition) or a polymer (by immersion or vapor coating) (Rihova, 2000;Johnston et al, 2005). The surface of noble metals can also be readily modified using a variety of self-assembled organic monolayers that are designed to reduce non-specific adsorption of proteins and subsequent biofilm formation (Ostuni et al, 2001).…”
Section: Cell Encapsulationmentioning
confidence: 99%